Sustainability Capacity of HIV/AIDS Programmes in Yogyakarta, Indonesia - Perigrinus Sebong; Dwi Handono Sulistio; Yodi Mahendradhata (International Journal of Public Health Science (IJPHS), 2017)
The Indonesian government established the prevalence target of HIV <0.50% in 2019 to control the spreading of HIV through the National Medium Term Development Plan. To ensure the sustainability of this development plan, a study of the strategic capacity of HIV/AIDS programmes is needed to provide an overview so that the program can be sustained over time. This study aimed to explore the sustainability capacity of HIV/AIDS programmes in Yogyakarta. This was a descriptive study utilizing a qualitative approach. The study involved 42 participants as key informants selected by a purposive sampling technique, and the data were examined using content analysis. By setting priorities of the local government supported by the Provincial Health Office and with the coordination of the Yogyakarta Province AIDS Commission, the programs are able to maintain sustainable HIV and AIDS programmes in Yogyakarta. Funding capacity, evaluation, programme adaptation and communication have not been optimal to ensure the sustainability. Stability of funding is the main obstacle to achieving the sustainability of HIV and AIDS programs. However, with good planning, partnership structure and sufficient organizational capacity, this approach can ensure the HIV and AIDS programmes will continue with the targets set by the Yogyakarta Provincial Health Office. The government in Yogyakarta needs to increase funding capacity, and improve communication to ensure sustainability. The strategy should include adaptation and evaluation of programs through strengthening private sector financing, formulating a communication plan and improving the capacity to respond to change.